Dual-Dipole UHF RFID Tag Antenna with Quasi-Isotropic Patterns Based on Four-Axis Reflection Symmetry - Chunfang Qin; Lingfei Mo; Hongliang Zhou; Hongjian Zhang (International Journal of Antennas and Propagation)
In many RFID practical applications, it is required that reader can effectively read tags which are placed in radiation covering area randomly. In this paper, a passive UHF dual-dipole tag antenna with quasi-isotropic patterns is designed, which can reduce the sensibility of tag read-orientation in a long distance. Two dipoles with four-axis reflection symmetric structure are used, and the two arms of the dipole are bent to fill the space of the antenna. In this way, a quasi-isotropic tag is easier to be obtained. The test results show that the gain deviation of the proposed antenna was less than 3.25 dB, and the maximum reading range in different directions was from 6.9 m to 10.0 m, with better quasi-isotropic performance and reading range than other commercial tags.